Effect of Different Treatments on Reduction of Oxalates in Starfruit (Averrhoa carambola) Juice (Tribhuvan University Journal of Food Science and Technology, 2022)
This study was aimed to evaluate the effect of EDTA blanching, NaCl blanching, and barley sprouts addition on the reduction of oxalates in starfruits juice. The effect of EDTA (0-0.6%), NaCl (0-10%), and sprouts (0-3%) treatments was evaluated by response surface methodology. EDTA, NaCl, and sprouts treatments had significant effects (p